Micrographic standarization of Baccharis L. species (Asteraceae) - Rodriguez, María Victoria (2013)
Controversies still exist regarding the differentiation of some Baccharis sect. Caulopterae species known as “carqueja”. In the present work we studied anatomically five of these species: Baccharis articulata (Ba), Baccharis crispa (Bc), Baccharis gaudichaudiana (Bg), Baccharis microcephala (Bm) and Baccharis trimera (Bt). Ba and Bc are considered official in Argentinean Pharmacopeia and Bt in the Brazilian Pharmacopeia. Bg and Bm are considering possible substitutes. The qualitative and quantitative variables for each one were determined, emphasizing the importance of anatomic characters as taxonomically useful. Analytical micrographs of the studied species were elaborated as reference standards for quality control of the raw drug.